Heavy Metal Removal by Fixed‐Bed Column – A Review. Issue 3 (28th May 2018) - Malik, Davendra Singh; Jain, Chakresh Kumar; Yadav, Anuj Kumar
Abstract: Industrial wastewater often contains heavy metals that, if not removed, pose a risk to the environment. Therefore, an extended overview of different methods for heavy metal removal by columns was conducted. Column studies are dependent on the flow rate, bed height and diameter, breakthrough curve, type of wastewater, and adsorbent. The fixed‐bed column is most commonly used for metal sequestration in aqueous media. Column studies have advantages due to industrial scale applicability and can treat large quantities of wastewater. Many kinetics models are applied in column studies like Adam‐Bohart, Yoon Nelson, Bed Depth/Service Time, Thomas, and Clark. This paper deals with the use of modified or non‐modified adsorbents for the treatment of metal‐laden water and wastewater by column technique. Abstract : Metal‐containing wastewater poses serious environmental risks. The most common method to remove the metals are fixed‐bed columns, due to their industrial‐scale application. This paper reviews the influences on the absorbent efficiency and kinetics models to describe the relationships of the different parameters.